Negative Stereotypes Cause Christians to Underperform in and Disidentify With Science. (November 2015) - Rios, Kimberly; Cheng, Zhen Hadassah; Totton, Rebecca R.; Shariff, Azim F.
Despite Christians being a religious majority in the United States, relatively few pursue higher education and careers in science. Our studies show that stereotypes about Christians being less competent in science than other groups are recognized by both Christians and non-Christians and are openly endorsed by non-Christians (Study 1). Our studies further demonstrate that when these stereotypes become salient, Christians are less interested in and identified with science (Study 2) and underperform on science-relevant tasks (Studies 3–5), compared to non-Christians. Even subtle contextual cues that bear more or less relevance to science are sufficient to compromise Christians' scientific task performance, particularly among the highly religious (Study 5). When these stereotypes are explicitly removed, however, performance differences between Christians and non-Christians disappear. These results suggest that Christians' awareness of the negative societal stereotypes about their group's scientific competence may be partially responsible for the underperformance and underrepresentation of Christians in scientific fields.